Analisis saluran pemasaran jagung manis (Zea mays saccharata) - Kamaludin; Dinar; Jaka Sulaksana (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Sweet corn is one of the leading commodities in Majalengka Regency. This study aims to find out: (1) What is the pattern of marketing channels and (2) How big is the marketing margin of sweet corn, (3) How big is the farmer's share and marketing efficiency. The method used is a descriptive method with a quantitative approach. The research area was selected purposively. Sampling technique is snowball sampling. Based on supervision there are 3 types of marketing channels, namely: (1) Sweet Corn Farmers – Retailers – Consumers, (II) Sweet Corn Farmers – Collector Traders – Retail Traders – Consumers, (III) Sweet Corn Farmers – Collector Traders I – Collector Traders II – Retail Traders – Consumers. The margin on marketing channel II is Rp. 3,000 and share is 41.66% Margin on marketing channel I is Rp.2,500 and share is 58.33%. The margin on marketing channel III is Rp. 2,600 and a share of 41.66%. Marketing efficiency in marketing channel I with a value of 21.66%, marketing channel II with a value of 22%, and marketing channel III with a value, 32%